Associations of The Gut Microbiota on Respiratory Disease in Children : A Systematic Review - Indah Dwi Lestari; Rifah Zafarani Soumena; Vina Zakiah Latuconsina; Octovina Toressy; Rahma Dyahnissa (International Medical Journal Corp. Ltd, 2026)
Background: The gut-lung axis represents a critical pathway linking early-life gut microbiota to pediatric respiratory diseases, but comprehensive synthesis of associations, mechanisms, and therapeutic evidence is lacking. Methods: This systematic review synthesized 80 studies (RCT, etc) examining gut microbiota associations with pediatric respiratory outcomes including asthma, allergic rhinitis, respiratory tract infections (RTIs), bronchiolitis, bronchopulmonary dysplasia (BPD), and cystic fibrosis (CF) lung disease. Results: Early-life gut dysbiosis during the first 100 days—characterized by reduced Lachnospira, Veillonella , Faecalibacterium , Rothia (FLVR taxa)—consistently associated with increased asthma risk (Arrieta et al., 2015). Short-chain fatty acids (SCFAs), particularly acetate and butyrate, emerged as central immunomodulatory mediators (Yang et al., 2025). Mendelian randomization confirmed causal roles for Collinsella and Ruminococcaceae UCG014 in childhood asthma (Li et al., 2023). In CF, Bifidobacterium - dominant gut microbiota associated with 45% fewer pulmonary exacerbations (Ray et al., 2022). Probiotics reduced RTI incidence (42% vs 59% in controls) and acute asthma exacerbations (RR 0.38) but showed no benefit for primary asthma prevention. Cesarean delivery, antibiotic exposure (HR for asthma 1.21), and breastfeeding cessation were key moderators. Apparent diversity–disease contradictions resolved when considering community composition rather than diversity metrics alone. Conclusion: Gut microbiota composition in early life is causally associated with pediatric respiratory disease risk through SCFA-mediated immune modulation, with the first 100 days as a critical window. Probiotics show strain-specific efficacy for RTI prevention and asthma treatment but not primary prevention.